Portuguese archives and libraries: a century of preservation and conservation practices for the control of biodeterioration - Casanova, Conceição; Pinheiro, Ana Catarina (Conservar Património, 2021)
Biodeterioration has been a central subject for libraries and archives. Throughout the ages, different preventive and curative conservation measures were adopted to manage biodeterioration in Portuguese institutions, but the problem persists. A historic review of different methodologies used to prevent biodeterioration in the Portuguese context is presented and compared to international trends. It focuses on theories and practices of paper conservation on par with their evolution and a comparison between the art collectors’ world and libraries and archives is also made. Biodeterioration management has always been a major concern, namely amid librarians and archivists, among the first ones to endorse the implementation of preservation policies. Although preservation awareness has a relatively long history, it is vital to encourage a better understanding of it at the decision-making level. In fact, the implementation of preventive conservation strategies continues to be unsatisfactory, despite the current sustainability issues and the dangers of handling contaminated documentation.   Received: 2020-1-23 Revised: 2020-4-28 Accepted: 2020-5-28 Online: 2020-5-28 Publication: 2021-2-10 A biodeterioração tem sido um assunto central para Bibliotecas e Arquivos. Ao longo do tempo, diferentes medidas de conservação preventiva e curativa foram adotadas para combater a biodeterioração nas instituições Portuguesas, mas o problema persiste. São revistas as diferentes metodologias usadas para prevenir a biodeterioração no cenário português e comparadas com as tendências internacionais. Focam-se as teorias e práticas da conservação de documentos gráficos, tendo em conta a sua evolução e é, ainda, estabelecido um paralelismo entre o mundo dos coleccionadores e a esfera dos arquivos ou bibliotecas. A gestão da biodeterioração tem-se mantido como preocupação central, nomeadamente entre bibliotecários e arquivistas, dos primeiros a implementar políticas de preservação. Apesar da reconhecida importância da preservação, é vital fomentar a sua compreensão ao nível da tomada de decisão. A implementação de estratégias de conservação preventiva continua a ser insatisfatória apesar dos actuais problemas de sustentabilidade e dos perigos no manuseamento de documentação contaminada.   Recebido: 2020-1-23 Revisto: 2020-4-28 Aceite: 2020-5-28 Online: 2020-5-28 Publicação: 2021-2-10